The impact toughness of novel keyhole TIG welded duplex stainless steel joints. (December 2018) - Cui, Shuwan; Shi, Yonghua; Cui, Yanxin; Zhu, Tao
Abstract: Keyhole tungsten inert gas (K-TIG) welding is a novel, high-efficiency welding method. In this study, 10.8-mm-thick duplex stainless steel (DSS) plates were welded via K-TIG welding, without groove preparation or filler metals. The microstructure, grain size and grain boundary misorientation angle distribution (GBMAD) of the weld metal (WM) were analyzed to characterize its impact toughness. Charpy impact tests were carried out, and the results proved that the impact absorbed energy (IAE) of the WM increases with the increase in heat input. This finding indicates that the austenite volume fraction and the GBMAD have an influence on the impact property of the WM. Highlights: K-TIG welding is a high efficiency and novel welding method, which successfully applied to S32101 duplex stainless steel. The microstructure of the austenite in the WM includes GBA, WA and IGA. The grain boundaries misorientation of the WMs were measured by using Electron backscatter diffraction technique. The microstructure, grain size and GBMAD of the WM were analyzed in order to discuss the impact toughness of the WM.